ANALYSIS OF STUDENT’S DIFFICULTIES IN LEARNING ENGLISH AT SMA NEGERI 1 BATAUGA - Elisa Dewi Sultra; Baharudin Baharudin (English Education Journal, 2020)
The purpose of this study was to determine the difficulties of eleventh grade students in learning English at SMA Negeri 1 Batauga. The research design uses a mixed-method design, which is used to describe students' difficulties in learning English. The research subjects were 12 students. The place of this research is SMA Negeri 1 Batauga. The research data were collected through test and interview. Data were analyzed based on the type of analysis by Miles and Huberman—data reduction, presentation, and conclusion or verification. Based on the data obtained in the field, especially the results of test and interview, it can be concluded that the level of students’ learning achievement of SMA Negeri 1 Batauga is low. And the factor that affects the difficulty of students in learning English is the motivation or low interest of students in learning English. This is indicated by their indifference or reluctance to learn English. This reluctance has an impact on their mastery of English, especially English vocabulary and grammar as well as their reading and speaking comprehension skills. This is because students of SMA Negeri 1 Batauga rarely repeat English lessons at home and do not memorize English vocabulary gradually. The results of the interview also showed that the students' environment did not have a positive influence on students in learning. That includes English teacher and parental support.